Psychiatric morbidities among patients with type-2 diabetes mellitus attending outpatient department in a rural area of North India - Mudassir Majeed; Rajiv K. Gupta; Rashmi Kumari; Bhavna Langer; Mehak T. Mir; Richa Mahajan; Riya Gupta; Jyoti Bala; Sakshi Manhas; Sumaira (Journal of Family Medicine and Primary Care)
Background: Both diabetes mellitus and psychiatric morbidities are widely prevalent diseases which show a discerning upward trend globally. Coexistence of diabetes and psychiatric morbidities usually manifests as impaired quality of life and poor treatment adherence. Objectives: The study aimed to estimate the prevalence of psychiatric morbidities among rural diabetic patients and to determine their association with different variables. Methodology: The present cross-sectional study was conducted in CHC of Rural Health Block attached with PG Department of Community Medicine GMC (Government Medical College) Jammu. The eligible diabetic patients attending medical outpatient department services were enrolled using a consecutive sampling method. DAS scale was used to assess psychiatric morbidity among the study subjects. Results: The findings revealed that the prevalence of psychiatric morbidity in the study participants was 38.9%, 68.5% and 25.64% for depression, anxiety and stress, respectively. Psychiatric morbidities were slightly higher in female patients and were significantly associated with age, marital status, sedentary lifestyle, history of substance abuse, duration of diabetes, presence of complications and underlying morbidities (P < 0.05). Conclusions: The prevalence of anxiety and depression among rural diabetic patients was found to be quite high. Diabetic patients need thorough screening for psychiatric evaluation, and there is an urgent need for psychiatric counselling at regular intervals.